KAJIAN PENGELOLAAN PESISIR DAN LAUT DENGAN SISTEM ZONASI DI KAWASAN KONSERVASI PERAIRAN DAERAH KECAMATAN LIUKANG TUPPABIRING - Hamzah MS; Rustam Rustam; Abdul Rauf (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2021)
Liukang Tuppabiring is a waters with marine biodiversity potential large enough to be developed and managed sustainably. Utilization around the coral reefs in the waters of the Liukang Tuppabiring sub-district currently tends to lead to destructive use, so it is necessary to take damage prevention measures immediately. The results showed the condition of coral cover in the medium and damaged, while at stations 1,2,3,4,6 (25,47-41.07%), while conditions were good at station 5 (56.20%). The number of individual reef fish is 290 individuals from 46 species of 22 genera 11 families. At the research location also identified one type of protected biota namely Hawksbill (Eretmochelys imbricata). Coral damage that occurred at 6 observation stations was more caused by the practice of using destructive and environmentally unfriendly fishing equipment such as bombs, trawls, and the use of poisons. The priority strategies undertaken in the management of coral reefs at the study site are 1) Management of environmentally friendly coral reefs where the community as a manager with strong support from the Government; 2) Making clear rules related to utilization in coral reef areas and establishing a POSMAKWAS institution to avoid more severe coral damage; 3) Improve supervision and law enforcement must be firm in relation to the use of fishing gear that can damage coral reef ecosystems.